2023
DOI: 10.3390/vaccines11040850
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives Associated with Human Papillomavirus Vaccination in Adults: A Qualitative Study

Abstract: Background: In the last several decades, vaccine hesitancy has become a significant global public health concern. The human papillomavirus (HPV) vaccine has been on the United States of America (USA) market since 2006, with extended approval up to age 45 granted in 2018. To date, there is limited research evaluating barriers and facilitators related to HPV vaccine initiation among adults and the influence of the COVID-19 pandemic on individuals’ vaccine-related behaviors. This study’s main objective was to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A recent study in the US found that participants identified the multi-dose series as inconvenient and a barrier to HPV vaccination. 22 Completion of the HPV vaccination series could be affected by the parent's attitude or lack of access to health care.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in the US found that participants identified the multi-dose series as inconvenient and a barrier to HPV vaccination. 22 Completion of the HPV vaccination series could be affected by the parent's attitude or lack of access to health care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the choice at the country level should also account for the health-economic objectives, the type of health infrastructure already in place as well as socio-cultural context. In some contexts, important arguments for choosing GN strategy could be the fact that it helps to overcome the stigma associated with a vaccine that targets only girls and aims to prevent a sexually transmitted disease ( Cernasev et al, 2023 ), and the direct health benefits in men who have sex with men.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection occurred from November 2021 to April 2022, when thematic saturation was achieved [22]. More information on data collection has been published in a previous manuscript [23].…”
Section: Methodsmentioning
confidence: 99%